Availability analysis of free-space-optical links based on rain rate and visibility statistics from tropical a climate - Basahel, Ahmed; Islam, Md Rafiqul; Ahmad Zabidi, Suriza; Habaebi, Mohamed Hadi (Elsevier, 2016)
Availability is one of the major parameters to measure the performance of Free Space Optics (FSO) communication link. In tropical climate, rainfall acts as a dominant factor that affects the FSO link availability; whereas haze has no significant effect compare with rain. But for longer FSO link distances, the effect of haze on the overall FSO link availability becomes serious and need to be considered. In this paper, availability of an FSO link is estimated under the impact of rain, haze and the combination of the two phenomena. The availability estimations based on predicted attenuation due to rain and haze using long-term statistical measurements of rain rate (mm/hr) and visibility (km) data measured in Malaysia. The effect of individual weather phenomena was demonstrated over FSO link ranges from 1 to 5 km. The combine effect of both rain and haze also has been analyzed using the cumulative distribution function (CDF) of predicted atmospheric attenuations. In tropical regions, for short FSO link distance, the influence of haze on the availability of FSO signal is negligible compare with rain; whereas for longer FSO distances, haze attenuation will reduce the overall link availability. This effect of haze needs careful consideration for the deployment of FSO systems especially in Malaysian tropical climates.